Gender Differences in the Labor Market: Impact of IRCA's Amnesty Provisions - Amuedo-Dorantes, Catalina; Bansak, Cynthia; Raphael, Steven (American Economic Review, 2007)
Gender Differences in the Labor Market: Impact of IRCA by Catalina Amuedo-Dorantes, Cynthia Bansak and Steven Raphael. Published in volume 97, issue 2, pages 412-416 of American Economic Review, May 2007